2010
DOI: 10.1002/art.27284
|View full text |Cite
|
Sign up to set email alerts
|

Biologic predictors of extension of oligoarticular juvenile idiopathic arthritis as determined from synovial fluid cellular composition and gene expression

Abstract: ObjectiveTo identify biomarkers in the first synovial fluid (SF) aspirate obtained from children with oligoarticular juvenile idiopathic arthritis (JIA), which could be used to identify children whose disease is likely to extend to a more severe phenotype.MethodsPatients with recent-onset oligoarticular JIA were identified and grouped according to those whose mild disease persisted (persistent disease) or those whose disease would extend from a mild to more severe phenotype (extended-to-be disease) at 1 year a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
49
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 47 publications
8
49
1
2
Order By: Relevance
“…CD8ϩ T cells accumulate in synovial tissue of JIA patients (21) and in the synovial fluid of adult patients with RA (22), while CD4ϩ T cells have been considered the predominant T cell population in the latter. Although the role of CD8ϩ T cells in the synovium is largely unknown, a recent study by Hunter et al demonstrated that in JIA, CD8ϩ T cells are recruited to the synovium by the chemokine RANTES, and once there, they become important sources of RANTES secretion (23). We found significantly elevated levels of RANTES both in the serum and in the patellar washouts from TC-PTP Ϫ/Ϫ mice.…”
Section: Discussionsupporting
confidence: 47%
“…CD8ϩ T cells accumulate in synovial tissue of JIA patients (21) and in the synovial fluid of adult patients with RA (22), while CD4ϩ T cells have been considered the predominant T cell population in the latter. Although the role of CD8ϩ T cells in the synovium is largely unknown, a recent study by Hunter et al demonstrated that in JIA, CD8ϩ T cells are recruited to the synovium by the chemokine RANTES, and once there, they become important sources of RANTES secretion (23). We found significantly elevated levels of RANTES both in the serum and in the patellar washouts from TC-PTP Ϫ/Ϫ mice.…”
Section: Discussionsupporting
confidence: 47%
“…6,20 Furthermore, in patients with JIA high levels of synovial fluid CD8 + T cells are correlated with a more progressive course of disease than is observed in patients with lower levels of these cells. 21 Specific T cell skewing in inflamed joints Notably, in the peripheral blood of patients with RA, the level of demethylation of Ifnγ and Il-17a is the same Key points ■ The study of immune regulation at the site of inflammation is required to improve our understanding of autoimmune pathology ■ At the site of autoimmune inflammation, proinflammatory mediators interfere with T-cell regulation and may induce T-cell plasticity ■ Regulatory T (T REG ) cells are less functional, or might even become pathogenic, in an autoimmune inflammatory environment, which should be kept in mind when developing T REG -cell-based therapies ■ Resistance of effector T cells to suppression markedly contributes to the disturbed immune balance in the inflamed joints of patients with arthritis ■ In autoimmune inflammation, a perpetuating loop exists in which antigen presenting cells (APCs) instruct T-cell differentiation and function, and effector T cells promote and shape the infiltration and differentiation of APCs as in healthy controls. 15 Thus, skewed CD4 + T-cell commit ment occurs specifically at the site of inflammation, likely as a result of an inter action between CD4 + T cells and local APCs, which are found in increased numbers in inflamed joints.…”
Section: T-cell Subsets In Autoimmune Arthritismentioning
confidence: 99%
“…55,56 In patients with JIA, unres ponsiveness to suppression was not only observed in CD4 + T cells, but also highly apparent in synovial fluid CD8 + T cells, 6 in line with their correlation to a more severe outcome of disease. 21 Furthermore, although this resistance to suppression is intrinsic to T cells and maintained in vitro even in the absence of synovial fluid APCs, 6 it seems that synovial fluid APCs are responsible for the initial induction of resistance to suppression in JIA (Wehrens et al unpublished observations).…”
Section: Resistance Of Effector T Cellsmentioning
confidence: 99%
“…Children were followed for 2 years after biopsies were taken. During this period children whose disease went on to involve more than four joints (after they had the disease for a total of six or more months) were re-classified as extended oligoarticular, ie, they were not extended at the time the biopsy was taken, this subgroup is referred to as ‘extended-to-be’24 from here on in. Clinical and demographic data are included in table 1.…”
Section: Methodsmentioning
confidence: 99%